Analysis of the Purpose and Principles of Learning Arabic - Herdah; Dasmarianti; Raodhatul Jannah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Arabic language learning has always faced problems in learning students caused by many factors, such as the learning content that does not match the student's conditions, the teacher's limited creativity in matching learning methods and strategies, the additional burden associated with the need to master the great skills of qira'ah that are not easy, and others. In addressing one of the problems of learning Arabic language, i.e. related to the methodology of Arabic learning, there is a need for discussion of the subject, in this article discussed about the understanding of the method of learning arabic language and its history, as well as the purposes and principles of learning the Arabic. This research uses a library study method for the purpose of studying, exploring, and as a reinforcer of this research. The Arabic language learning methodology is a method used by teachers in teaching Arabic materials so that the materials can be delivered and well understood by the students, the method of language learning has evolved over time and started since the 1980s. The purpose of learning Arabic in each school has its own characteristics, but in general, the main goal of Arabic learning is to improve language competence, communication competence and culture. Before learning Arabic, educators should pay close attention to and understand the principles of Arabic learning, including priority, accuracy, motivation, graduation, and validation.